2006
DOI: 10.1007/0-387-34226-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Call for Quality: Open Source Software Quality Observation

Abstract: Abstract. This paper describes how a Software Quality Observatory works to evaluate and quantify the quality of an Open Source project. Such a quality measurement can be used by organizations intending to deploy an Open Source solution to pick one of the available projects for use. We offer a case description of how the Software Quality Observatory will be applied to the KDE project to document and evaluate its quality practices for outsiders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It is not clear that these factors, even when combined, would give an adequate definition of quality. As a result many researchers have used different project characteristics as a substitute measure of the quality of a project, including longevity [13], operational software characteristics [31], number of open bugs [5], etc. None of these properties measure code quality directly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear that these factors, even when combined, would give an adequate definition of quality. As a result many researchers have used different project characteristics as a substitute measure of the quality of a project, including longevity [13], operational software characteristics [31], number of open bugs [5], etc. None of these properties measure code quality directly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They advocated the necessity of usability awareness among OSS developers. De Groot et al [10] observed that not only has the participation grown in OSS development, but number of users and their requirements have increased tremendously as well in the last decade. The authors mentioned that although dozens of OSS applications are available, which differ in quality features and requirements, the end user finds it very difficult to choose one for a given problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Users and developers are limited resources within the OSS environment, particularly so with regards to develoeprs [8]. However, several major OSS projects have been noted to be particularly successful at recruiting new developers [16,17].…”
Section: Mean Developer Engagementmentioning
confidence: 99%